Assessment of phytotoxicity of treated water of Tabuk wastewater plant by different technologies on seed germination of chick pea (Cicer arietinum) - Zahid Hameed Siddiqui (IWA Publishing, 2021)
The use of reclaimed water as an alternative source is a sustainable way forward for an arid country like The Kingdom of Saudi Arabia. The sewage contains organic and inorganic pollutants from households and industrial sources that may not be removed during treatment. In this study, seeds of Cicer arietinum were germinated using six different concentrations of treated water from the Tabuk wastewater treatment plant and tap water was used as control. The physicochemical properties such as total dissolved solids, electrical conductivity, total suspended solids, and turbidity values of treated water were higher, which gradually decreased on dilution with tap water. The amount of ammonia, nitrite, nitrate, and phosphate was in higher concentration in treated water as compared to control. The use of 40% treated water (T3) improved the germination percentage, speed of germination and germination index of C. arietinum. The phytotoxicity test reveals that undiluted treated water (T6) is not fit for direct use on plants. All the investigated treatments confirmed that the use of more than 40% of treated water decreased the fresh weight and dry weight of the seedlings as compared to control. The results are encouraging and help in attaining water sustainability in the Tabuk region. HIGHLIGHTS In KSA agricultural practices are difficult to carry out due to water scarcity.; To our best knowledge, this is the first report of the use of reclaimed water of Tabuk wastewater treatment plant in a seed germination-based experiment.; All the investigated parameters confirmed that the use of more than 40% of treated water is not fit for direct use on plants.; The results are encouraging and help in attaining water sustainability in the Tabuk region.; It also decreases the load of desalination of the Red Sea and helps to fulfil the sustainable development goals of VISION 2030 of KSA.;